Sensory Analysis and Consumer Research in New Product Development - Ruiz-Capillas, Claudia; Herranz, Ana Herrero (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Sensory analysis and consumer research are relevant tools in innovation andnew product development, from design to commercialization. This Special Issuehas collected 13 valuable scientific contributions, including 1 review, 12 originalresearch articles and an editorial. The SI provides an interesting outlookand better understanding of sensorial analysis with the different techniques andconsumer research on new product development. Important practical applicationshave been reported on the development of different novel, functional andenhanced products (meat, fish, biscuits, yogurt, porridge, hybrid meat, molecularproducts, etc.), which helps increase knowledge in this field. This SI isvery useful for both present and future uses for the different players involved inthis kind of product development (industry, companies, researchers, scientists,marketing, merchandising, consumers, etc.).